Strength and Conditioning for team sports - Gamble, P. (Routledge, 2009)
Drawing on the very latest scientific research, Strength and Conditioning for Team Sports is designed to help students, coaches, researchers and sports medicine professionals devise more effective high-performance training programs for team sports. The only evidence-based study of sport-specific practice for team sports, this book introduces the core science underpinning any strength and conditioning regime, combining the best of applied physiology, biomechanics, sports medicine and coaching science.